Transactional memory in Ronnie Govender's At the Edge and other Cato Manor Stories. Issue 1 (2nd January 2016) - Chetty, Rajendra
Abstract : Ronnie Govender's text, At the Edge and other Cato Manor Stories (1996. Pretoria: Hibbard Publishers), regarded here as a text-site of memory, is significant in the construction of South Africa's national identity. The collection of short stories recalls the resilience of the multiracial community of Cato Manor, whose democratic co- existence and mutual respect comprise a model for the national democratic character of today. As a record of the ills of the past, Govender's text enables South Africans to confront and come to terms with issues such as indenture, colonialism and apartheid. Govender's unique performative prose revivifies the lives of the residents of Cato Manor, an area whose history is neglected compared with those of District Six or Sophiatown. This resuscitation of Cato Manor characters in this dramatic form facilitates the memory work of Govender's writing and performance. The new national identity recognizes the roles played by all communities past and present. Govender's work constitutes a major part of the construction of that identity, in speaking for his particular community, their contribution to the country and its struggle for freedom. In the course of recognizing the national significance of Govender's texts, this article traces defining generic intersections between theatricality, the short story and memory studies.